Low-Temperature Conductivity Study of Multiorganic Solvent Electrolyte for Lithium-Sulfur Rechargeable Battery Application - Ravindar Dharavath; Ashwin Murali; Abdul Wasi Tarapathi; Balasubramanian Trichy Srinivasan; Rambabu Kammili (International Journal of Electrochemistry)
The conductivity of an electrolyte plays a significant role in deciding the performance of any battery over a wide temperature range from −40°C to 60°C. In this work, the conductivity of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) at a varied salt concentration range from 0.2 M to 2.0 M in a multisolvent organic electrolyte system over a wide temperature range from −40°C to 60°C is reported. The mixed solvents used were 1,3-dioxolane (DOL), 1,2-dimethoxyethane (DME), and tetraethylene glycol dimethyl ether (TEGDME) with an equal ratio of DOL : DME : TEGDME (1 : 1 : 1 by volume). The experimental analysis performed over a wide temperature range revealed the maximum conductivity at salt concentrations ranging from 1.0 M to 1.4 M for equal molar solvents. The optimum salt concentration and maximum conductivity in a different solvent composition ratio (i.e., 3 : 2 : 1) for all the temperatures is reported herein. The temperature-dependence conductivity of the salt concentration did not fit the Arrhenius plot, but it resembled the Vogel–Tamman–Fulcher plot behavior. The present conductivity study was carried out to evaluate the overall operable temperature limit of the electrolyte used in the lithium-sulfur battery.